Claw the giant monkey - Blade, Adam (Orchard London, 2015)
Avantia is under threat from an evil wizard. To save the kingdom, Tom must defeat six terrifying Beasts and collect the pieces of magical golden armour. Join Tom as he journeys into the Dark Jungle to do battle with Claw the Giant Monkey!